MENIMBANG UPACARA ADAT NOIâAN RUMAH KE DALAM KEBAKTIAN KRISTIANI - Yosefa, Wilfrida Ade; Jelahu, Timotius Tote (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
The authors raised the wisdom of Noiâan house in Dayak Blaman community as an example of indigenous peoples that live in peace with all the elements of nature creation. Noiâan house is one of the traditional ceremonies as a greatful expression and begged the protection of Sangiang Dewata for new house and the people who live in the house. It is hoped that the Church can always be united and continue to voice the gospel in everyday life, especially in cultural life. Churches and catechists should be able to inculturate local cultural wisdom with the Christian faith.